PERFORMA FINANSIAL ITIK PETELUR POLA PEMELIHARAAN SEMI INTENSIF (Survey Di Kecamatan Sukra Kabupaten Indramayu) - Linda Herlina; Anita Fitriani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The laying duck business has the potential to be developed, so that it can provide additional income in its business. This study aims to analyze the average cost, revenue, income and business efficiency of laying ducks in Sukra District, Indramayu Regency. This research was conducted in April 2022. The research method used in this study was a survey method for 41 respondents. The data used are primary data and secondary data, where primary data is intended to obtain data information from the main source, namely laying duck farmers as respondents through interviews using questionnaires. Secondary data were obtained from the study of literature related to the research. The results showed that with an average ownership of 345 laying ducks, the average cost was 122,638,091 IDR per year, the average income was 153,148,244 IDR per year, the average income is 30,510,153 IDR per year and the level of business efficiency obtained is 1.25